2011
DOI: 10.1080/01416200.2011.546669
|View full text |Cite
|
Sign up to set email alerts
|

European religious education teachers' perceptions of and responses to classroom diversity and their relationship to personal and professional biographies

Abstract: and Norway. It presents a study of the teachers' perceptions of and responses to the diversity within their classes, in relation to their professional role and their personal and professional biographies. The study employed biographical research methods and 36 teachers were interviewed. Key findings were that, in every country, there was a clear relationship between individual teachers' personal biographies and how they responded to religious and/or cultural diversity and common cross-national strategies for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 4 publications
0
15
0
1
Order By: Relevance
“…Lisa and Sara focus on the similarities. Their preparedness to encounter the prejudices of other cultures and their distanced approaches to different ways of understanding life is to some extent comparable with the teachers in the REDCO project and their playing down of religious differences in the classroom (Everington et al 2011). This approach to the connections between the religions is one that is also used by Emil, who at the beginning of the interview talks about religions in terms of different sociocultural tracks.…”
Section: Smentioning
confidence: 91%
See 1 more Smart Citation
“…Lisa and Sara focus on the similarities. Their preparedness to encounter the prejudices of other cultures and their distanced approaches to different ways of understanding life is to some extent comparable with the teachers in the REDCO project and their playing down of religious differences in the classroom (Everington et al 2011). This approach to the connections between the religions is one that is also used by Emil, who at the beginning of the interview talks about religions in terms of different sociocultural tracks.…”
Section: Smentioning
confidence: 91%
“…In the project, four scholars (Everington et al 2011) studied RE teachers' approaches to diversity in England, France, Germany, the Netherlands and Norway. One general conclusion was that:…”
Section: Re Teachers and Pluralismmentioning
confidence: 99%
“…A desire to create a classroom atmosphere of trust and openness was found to be a common theme in the responses of RE teachers from six European countries who participated in a study of teaching about and in situations of diversity (Van der Want et al 2009;Everington et al 2011). This suggests that, despite different national understandings of the subject, there may be a particular need in RE to decrease traditional teacher-pupil 'distance'.…”
Section: Second-year Research Questions and Methodsmentioning
confidence: 97%
“…They find that whereas teachers and pupils sometimes present strong differences in personal commitment towards religion or pluralism, they also share perceptions and attitudes that are strengthened by the school environment. Everington et al 19 showed that the way secondary education teachers address religious diversity issues is at the crossroads of their personal perceptions of these issues, their personal biographies, and national educational policies.…”
Section: A Brief Overview Of the State Of The Artmentioning
confidence: 99%